Clinical relevance of vitamin B12 level and vitamin B12 metabolic gene variation in pulmonary tuberculosis - Zhang, Tian-Ping; Li, Rui; Wang, Li-Jun; Tang, Fei; Li, Hong-Miao (Frontiers in Immunology, 2022)
The aim of this study was to assess the association of vitamin B12 level and single nucleotide polymorphisms (SNPs) in vitamin B12 metabolic genes with pulmonary tuberculosis (PTB) in Chinese Han population. The plasma vitamin B12 expression level was detected using ELISA. Ten SNPs in six key genes (TCN1, TCN2, CUBN, MMACHC, FUT6, MUT) of vitamin B12 metabolic pathway were included for genotyping by the SNPscan technique among 454 PTB patients and 467 controls. Our results found that vitamin B12 level was significantly reduced in PTB patients when compared to controls. There was no significant association between TCN1 rs526934, TCN2 rs1801198, CUBN rs7906242, rs10904861, rs1801222, MMACHC rs10789465, FUT6 rs3760776, rs3760775, MUT rs9473555, rs9381784 variants and PTB susceptibility. TCN2 rs1801198 CC genotype, C allele were significantly associated with hypoproteinemia in PTB patients. In CUBN, rs7906242 GG genotype, G allele, rs10904861 TT genotype, T allele were significantly related to the decreased frequency of sputum smear-positive, and rs10904861 variant was affected the occurrence of drug resistance in PTB patients. In addition, the increased frequency of CUBN rs1801222 AA genotype was significantly associated with leukopenia. The decreased frequency of MUT rs9473555 CC genotype was found in the PTB patients with hypoproteinemia. However, vitamin B12 expression was not associated with the genotype distribution of above SNPs. In conclusion, vitamin B12 level was significantly decreased in PTB patients and genetic variants in vitamin B12 metabolic genes were not contribute to PTB susceptibility. Several SNPs in TCN2, CUBN, MUT gene might associate with multiple clinical manifestations in PTB.